The Potential of Zero-Carbon Bunker Fuels in Developing Countries - Englert, Dominik; Losos, Andrew; Raucci, Carlo; Smith, Tristan (World Bank, Washington, DC, 2021)
To meet the climate targets set forth in the International Maritime Organization’s Initial GHG Strategy, the maritime transport sector needs to abandon the use of fossil-based bunker fuels and turn toward zero-carbon alternatives which emit zero or at most very low greenhouse gas (GHG) emissions throughout their lifecycles. This report, “The Potential of Zero-Carbon Bunker Fuels in Developing Countries”, examines a range of zero-carbon bunker fuel options that are considered to be major contributors to shipping’s decarbonized future: biofuels, hydrogen and ammonia, and synthetic carbon-based fuels. The comparison shows that green ammonia and green hydrogen strike the most advantageous balance of favorable features due to their lifecycle GHG emissions, broader environmental factors, scalability, economics, and technical and safety implications. Furthermore, the report finds that many countries, including developing countries, are very well positioned to become future suppliers of zero-carbon bunker fuels—namely ammonia and hydrogen. By embracing their potential, these countries would be able to tap into an estimated $1+ trillion future fuel market while modernizing their own domestic energy and industrial infrastructure. However, strategic policy interventions are needed to unlock these potentials.